A method for preparing corundum-mullite refractory material by adding fused quartz

By using raw materials such as alumina and fused quartz, combined with AlN-SiC solid solution ultrafine powder as a sintering aid, corundum-mullite refractory materials are prepared, which solves the problems of volume expansion and thermal shock stability caused by the phase change of natural silica, and achieves Preparation of materials with high strength and high thermal shock resistance.

CN118684507BActive Publication Date: 2025-01-21101 INST OF THE MINISTRY OF CIVIL AFFAIRS
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410829716.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2025-01-21
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

The existing corundum-mullite refractory materials have large volume expansion due to natural silica phase change during high-temperature firing, which is difficult to burn, and the thermal shock stability performance is not ideal.

Method used

Alumina and fused quartz are used as raw materials, and AlN-SiC solid solution ultrafine powder is used as a sintering aid. Corundum-mullite refractory materials are prepared through high-temperature sintering to avoid volume expansion caused by quartz phase change and fill the pores with a high-viscosity glass phase. Improve thermal shock stability.

Benefits of technology

The preparation of corundum-mullite refractory materials with zero expansion, high density, high strength and high thermal shock resistance has been achieved. The linear expansion rate after burning is low, the thermal shock stability is excellent, and it is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118684507B_ABST
    Figure CN118684507B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a corundum-mullite refractory material by adding fused quartz, and belongs to the technical field of refractory materials. The raw materials of the corundum-mullite material of the present invention are calculated by mass, including: 70-94 parts of aluminum oxide, 5-27 parts of fused quartz, 1-3 parts of AlN-SiC solid solution ultrafine powder and 3-5 parts of PVA solution binder. In view of the problems of large volume expansion caused by natural silica phase change in the prior art, large difficulty in firing of corundum-mullite refractory materials, and unsatisfactory thermal shock stability, the present invention selects aluminum oxide and fused quartz as raw materials, and AlN-SiC solid solution ultrafine powder as a sintering aid, so as to realize the preparation of a corundum-mullite refractory material with zero expansion, high density, high strength and high thermal shock resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, in particular to a method for preparing a corundum-mullite refractory material by adding fused quartz. Background Art

[0002] The main high-temperature crystal phases of corundum-mullite refractory materials are corundum and mullite. The crystals of corundum are short columnar and barrel-shaped, and do not intersect or interlace with each other in the refractory structure. Embedding interlaced columnar crystals of mullite between corundum crystals can effectively prevent the slip of corundum crystals, obtain a stable structure, and be more conducive to the excellent performance of mullite and corundum. For example, the melting point of corundum is about 2050℃, and the melting point of mullite is about 1850℃. The thermal expansion coefficient and thermal conductivity of corundum are basically the same as those of mullite. The physical properties of the two are matched. Compounding corundum and mullite to form a corundum-mullite composite material can improve the high-temperature mechanical properties of the material, especially the high-temperature creep properties. In the prior art, when studying the high-temperature performance of the corundum-mullite system, it was proposed that the optimal ratio of the two crystal phases is 75:25 or 25:75, which is better than the performance of a single material. This is because at this ratio, the grains are intertwined and filled with each other, interspersed into a network structure, and the crystals are combined into a good framework structure, thus having excellent strength and creep resistance.

[0003] Mullite in corundum-mullite refractory can be pre-synthesized mullite, in-situ synthesized mullite or secondary mullite. my country has abundant silica resources. When in-situ synthesized mullite is used to prepare corundum-mullite refractory, corundum and natural silica are usually used as raw materials and fired at high temperature. Natural silica is mainly quartz phase, such as Figure 1 As shown in the figure, the thermodynamic stability range of quartz is from low temperature to 870℃. When the temperature is higher than 870℃, it transforms into tridymite, and when the temperature is higher than 1470℃, it further transforms into cristobalite. During the heating process, as the temperature rises, SiO2 undergoes a crystal transformation, accompanied by a certain volume change: when α-quartz transforms into α-tridymite, it is accompanied by a linear expansion of 4.57%, which is converted into a volume expansion of up to 13.7%. When α-quartz transforms into α-cristobalite, it is accompanied by a linear expansion rate of 6%, and the volume expansion rate is as high as 17.4%. Therefore, when corundum and silica are used as raw materials to synthesize corundum-mullite refractory materials, during the high-temperature firing process, silica first undergoes a phase transformation from quartz to cristobalite, resulting in a large volume expansion; cristobalite further reacts with corundum to generate mullite in situ. The inevitable quartz phase transformation during high-temperature firing makes the firing of corundum-mullite materials difficult, and the product has a low volume density, and the high-temperature strength and thermal shock stability are not ideal, which still needs further improvement. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a corundum-mullite refractory material by adding fused quartz. In view of the problems existing in the prior art, such as large volume expansion caused by natural silica phase change, great difficulty in sintering the corundum-mullite refractory material, and unsatisfactory thermal shock stability, the present invention selects alumina and fused quartz as raw materials and AlN-SiC solid solution ultrafine powder as a sintering aid, thereby realizing the preparation of a corundum-mullite refractory material with zero expansion, high density, high strength and high thermal shock resistance.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a corundum-mullite material, wherein the raw materials, calculated by weight, include:

[0007] 70-94 parts of alumina, 5-27 parts of fused quartz, 1-3 parts of AlN-SiC solid solution ultrafine powder and 3-5 parts of PVA solution binder.

[0008] Fused quartz is made by heating and melting natural pure quartz or crystal at a temperature above its melting point into a thick transparent melt, and then cooling it. It has the advantages of stable quality and high purity. Using fused quartz as a silicon source and sintering at high temperature to prepare corundum-mullite refractory materials can avoid the large volume expansion caused by the quartz reconstruction phase change; at the same time, fused quartz is partially transformed into amorphous SiO2 with high viscosity at high temperature, which is conducive to the generation of closed pores in the product of the present invention, thereby effectively improving the thermal shock stability of the material.

[0009] Preferably, the particle size of the aluminum oxide is ≤3 mm; the particle size of the fused quartz is ≤100 μm; and the particle size of the AlN—SiC solid solution ultrafine powder is ≤5 μm.

[0010] Preferably, in the AlN—SiC solid solution ultrafine powder, the mass ratio of aluminum nitride to silicon carbide is 2:98 to 98:2.

[0011] Preferably, the PVA solution binder is a polyvinyl alcohol aqueous solution with a concentration of 3-20 wt.%.

[0012] The second technical solution of the present invention is to provide a method for preparing the above-mentioned corundum-mullite material, comprising the following steps:

[0013] Weigh the raw materials according to the proportion, mix them evenly, and make a clay material;

[0014] The mud material is pressed into shape, dried, and sintered to complete the preparation.

[0015] Preferably, the drying is performed to a moisture content of less than 1.5 wt.%.

[0016] More preferably, the drying temperature is 50-150° C. and the drying time is 10-48 hours.

[0017] Preferably, the sintering temperature is 1550-1750° C. and the sintering time is 5-15 hours.

[0018] The third technical solution of the present invention is to provide an application of the above-mentioned corundum-mullite material in the field of refractory materials.

[0019] The beneficial technical effects of the present invention are as follows:

[0020] During the high-temperature sintering process of AlN-SiC solid solution ultrafine powder, it is gradually oxidized to generate a glassy mixture of aluminum oxide and silicon dioxide (SiO2-Al2O3), which realizes liquid phase sintering and promotes the conversion rate of mullite and material densification; further, during the high-temperature sintering process, the glassy mixture of aluminum oxide and silicon dioxide (SiO2-Al2O3) gradually crystallizes and precipitates micro-nano mullite grains, which plays a role in particle dispersion reinforcement and greatly improves the high-temperature strength of the material. Therefore, using AlN-SiC solid solution ultrafine powder as a sintering aid, dispersed mullite grains can be synthesized in situ as a reinforcement phase to improve the strength of the material.

[0021] During the high-temperature firing process, part of the molten quartz is converted into cristobalite (1050°C), and then part of the cristobalite begins to mullite (1500°C); at the same time, part of the molten quartz is converted into an amorphous high-viscosity glass phase, which fills the large pores and voids in the body (1550°C), inhibiting the anisotropic growth of mullite crystals; the high-viscosity glass phase reacts with alumina and is completely converted into mullite, generating irregular granular mullite and forming a large number of closed pores (1600°C).

[0022] In view of the problems existing in the prior art such as large volume expansion caused by phase change of natural silica, great difficulty in sintering corundum-mullite refractory materials, and unsatisfactory thermal shock stability, the present invention selects alumina and fused quartz as raw materials and AlN-SiC solid solution ultrafine powder as a sintering aid to achieve the preparation of corundum-mullite refractory materials with extremely low expansion, high strength and high thermal shock resistance.

[0023] It has been measured that the corundum-mullite material prepared by the present invention has high strength (≥150MPa), excellent thermal shock resistance (1100°C water cooling ≥30 times), low linear expansion rate after firing (<0.1%), strong controllability of firing process, high production efficiency, suitability for industrial production, high product qualification rate, and good application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 Schematic diagram of the preparation process of Examples 1-5.

[0026] Figure 2 The microscopic morphology of the product of Example 2. (a) and (b) are microscopic morphology of the high viscosity amorphous phase and the mullite and closed pores, respectively.

[0027] Figure 3 These are microscopic morphology images of the product of Example 2 at different positions and different magnifications.

[0028] Figure 4 To verify the effect 1, the X-ray diffraction patterns of the samples sintered at different temperatures. DETAILED DESCRIPTION

[0029] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0030] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0031] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0032] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0033] The particle size of the aluminum oxide used in the following embodiments and comparative examples of the present invention is ≤3 mm; the particle size of the fused quartz used is ≤100 μm; the mass ratio of aluminum nitride to silicon carbide in the AlN-SiC solid solution ultrafine powder used is 20:80, and the particle size is ≤5 μm; the PVA solution binder used is a polyvinyl alcohol aqueous solution with a concentration of 12 wt.%; the particle size of the natural silica used is ≤100 μm.

[0034] The "room temperature" in the present invention is 20-30°C unless otherwise specified.

[0035] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.

[0036] Figure 1 Schematic diagram of the preparation process of Examples 1-5.

[0037] Example 1

[0038] The raw materials of corundum-mullite refractory materials are composed of the following raw materials by mass:

[0039] 94 parts of alumina, 5 parts of fused quartz, 1 part of AlN-SiC solid solution ultrafine powder and 3 parts of PVA solution binder.

[0040] Preparation of corundum-mullite refractory materials:

[0041] The raw materials are mixed evenly and then pressed into a shape. After being dried to a water content of less than 1.5 wt.%, they are placed in a tunnel kiln and kept at 1650° C. for 5 hours to obtain a corundum-mullite refractory material.

[0042] The product of this embodiment has an apparent porosity of 14.3% and a bulk density of 3.05 g / cm 3 The room temperature compressive strength (tested according to the national standard GBT 5072-2008) is 157MPa, the linear expansion rate after firing is 0.05%, and the number of thermal shock stability cycles (1100℃, water cooling) is ≥30 times.

[0043] Example 2

[0044] The raw materials of corundum-mullite refractory materials are composed of the following raw materials by mass:

[0045] 93 parts of alumina, 5 parts of fused quartz, 2 parts of AlN-SiC solid solution ultrafine powder and 4 parts of PVA solution binder.

[0046] Preparation of corundum-mullite refractory materials:

[0047] The raw materials were mixed evenly and then pressed into shape. After being dried to a water content of less than 1.5 wt.%, they were placed in a tunnel kiln and kept at 1650° C. for 10 hours to obtain a corundum-mullite refractory material.

[0048] The product of this embodiment has an apparent porosity of 15.9% and a bulk density of 3.00 g / cm 3 The room temperature compressive strength is 219MPa, the linear expansion rate after firing is 0.04%, and the number of thermal shock stability cycles (1100℃, water cooling) is ≥40 times.

[0049] Figure 2 The microscopic morphology of the product of Example 2. (a) and (b) are microscopic morphology of the high viscosity amorphous phase and mullite and closed pores, respectively. Figure 2 It can be seen that the formation of a high-viscosity glassy intermediate phase after sintering of fused quartz produces a certain amount of closed pores inside the product, which can improve the thermal shock resistance of the material. The mullite marked in (b) refers to the mullite precipitated in the closed pores.

[0050] Figure 3 The microscopic morphology of the product of Example 2 at different positions and different magnifications. Among them, the yellow-marked parts in (a) and (c) represent the microscopic morphology of the parts where micro-nano mullite grains are precipitated.

[0051] Example 3

[0052] The raw materials of corundum-mullite refractory materials are composed of the following raw materials by mass:

[0053] 85 parts of alumina, 12 parts of fused quartz, 3 parts of AlN-SiC solid solution ultrafine powder and 4 parts of PVA solution binder.

[0054] Preparation of corundum-mullite refractory materials:

[0055] The raw materials are mixed evenly and then pressed into shape. After being dried to a water content of less than 1.5 wt.%, the raw materials are placed in a tunnel kiln and kept at 1700° C. for 12 hours to obtain a corundum-mullite refractory material.

[0056] The product of this embodiment has an apparent porosity of 15.1% and a bulk density of 2.97 g / cm 3 The room temperature compressive strength is 189MPa, the linear expansion rate after firing is 0.07%, and the number of thermal shock stability cycles (1100℃, water cooling) is ≥40 times.

[0057] Example 4

[0058] The raw materials of corundum-mullite refractory materials are composed of the following raw materials by mass:

[0059] 78 parts of alumina, 20 parts of fused quartz, 2 parts of AlN-SiC solid solution ultrafine powder and 5 parts of PVA solution binder.

[0060] Preparation of corundum-mullite refractory materials:

[0061] The raw materials are mixed evenly and then pressed into shape. After being dried to a water content of less than 1.5 wt.%, the raw materials are placed in a tunnel kiln and kept at 1700° C. for 15 hours to obtain a corundum-mullite refractory material.

[0062] The product of this embodiment has an apparent porosity of 16.4% and a bulk density of 2.92 g / cm 3 The room temperature compressive strength is 166MPa, the linear expansion rate after firing is 0.07%, and the number of thermal shock stability cycles (1100℃, water cooling) is ≥40 times.

[0063] Example 5

[0064] The raw materials of corundum-mullite refractory materials are composed of the following raw materials by mass:

[0065] 70 parts of alumina, 27 parts of fused quartz, 3 parts of AlN-SiC solid solution ultrafine powder and 4 parts of PVA solution binder.

[0066] Preparation of corundum-mullite refractory materials:

[0067] The raw materials are mixed evenly and then pressed into shape. After being dried to a water content of less than 1.5 wt.%, they are placed in a tunnel kiln and kept at 1700° C. for 15 hours to obtain a corundum-mullite refractory material.

[0068] The product of this embodiment has an apparent porosity of 15.6% and a bulk density of 2.81 g / cm 3 The room temperature compressive strength is 181MPa, the linear expansion rate after firing is 0.06%, and the number of thermal shock stability cycles (1100℃, water cooling) is ≥40 times.

[0069] Comparative Example 1

[0070] The raw materials of corundum-mullite refractory materials are composed of the following raw materials by mass:

[0071] 93 parts of alumina, 7 parts of natural silica and 4 parts of PVA solution binder.

[0072] Preparation of corundum-mullite refractory materials:

[0073] The raw materials were mixed evenly and then pressed into shape. After being dried to a water content of less than 1.5 wt.%, they were placed in a tunnel kiln and kept at 1650° C. for 10 hours to obtain a corundum-mullite refractory material.

[0074] The test results show that the apparent porosity of the product of this comparative example is 16.6% and the bulk density is 3.08 g / cm 3 The room temperature compressive strength is 72MPa, the linear expansion rate after firing is 1.2%, and the number of thermal shock stability cycles (1100℃, water cooling) is 25 times.

[0075] Comparative Example 1 uses natural silica as the silicon source, and its main crystal phase is quartz. During the high-temperature firing process, quartz transforms into cristobalite, accompanied by a large volume expansion. The post-firing linear expansion rate of the material is as high as 1.2%; at the same time, there is no AlN-SiC solid solution ultrafine powder to generate a highly active and highly viscous liquid phase sintering aid during the sintering process, densification is difficult, the sample has few closed pores, and the pore diameter is large. Therefore, the thermal shock stability is insufficient.

[0076] Comparative Example 2

[0077] The only difference from Example 2 is that the addition of AlN—SiC solid solution ultrafine powder is omitted.

[0078] The test results show that the apparent porosity of the product of this comparative example is 20.1% and the volume density is 2.67 g / cm 3 The room temperature compressive strength is 75MPa, the linear expansion rate after firing is 1.4%, and the number of thermal shock stability cycles (1100℃, water cooling) is 16 times.

[0079] Comparative Example 3

[0080] The only difference from Example 2 is that the fused quartz is replaced by natural silica of equal mass.

[0081] The test results show that the apparent porosity of the product of this comparative example is 22.1% and the volume density is 2.78 g / cm 3 The room temperature compressive strength is 73MPa, the linear expansion rate after firing is 2.7%, and the number of thermal shock stability cycles (1100℃, water cooling) is 11 times.

[0082] Effect verification 1

[0083] By only changing the temperature of the sintering step in Example 2 to 1300°C, 1400°C, 1500°C, 1600°C or 1700°C, the obtained refractory material samples were tested for X-ray diffraction patterns. The test results are as follows: Figure 4 shown.

[0084] Figure 4 The X-ray diffraction patterns of the samples sintered at different temperatures in effect verification 1 are shown below. Figure 4 It can be seen that during the high-temperature sintering process, part of the fused quartz is converted into cristobalite. At 1500°C, part of the cristobalite begins to mullite. At 1600°C, the high-viscosity glass phase reacts with alumina and is completely converted into mullite.

[0085] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A corundum-mullite material, characterized in that: The raw materials are calculated by mass: 70-94 parts of alumina, 5-27 parts of fused quartz, 1-3 parts of AlN-SiC solid solution ultrafine powder and 3-5 parts of PVA solution binder; The method for preparing the corundum-mullite material comprises the following steps: Weigh the raw materials according to the proportion, mix them evenly, and make a clay material; The clay material is pressed into shape, dried, and sintered to complete the preparation; The sintering temperature is 1650-1750°C and the sintering time is 5-15h; The particle size of the AlN-SiC solid solution ultrafine powder is ≤5 μm; the mass ratio of aluminum nitride to silicon carbide in the AlN-SiC solid solution ultrafine powder is 20:

80.

2. The corundum-mullite material according to claim 1, characterized in that: The particle size of the aluminum oxide is ≤3 mm; the particle size of the fused quartz is ≤100 μm.

3. The corundum-mullite material according to claim 1, characterized in that: The PVA solution binder is a polyvinyl alcohol aqueous solution with a concentration of 3-20wt.%.

4. The corundum-mullite material according to claim 1, characterized in that: The drying is performed to a moisture content of less than 1.5 wt.%.

5. Use of the corundum-mullite material according to any one of claims 1 to 4 in the field of refractory materials.

Citation Information

Patent Citations

  • Method for production of corundum-mullite ceramics scnalox-mc

    RU2054396C1